Primary tumor location and survival in colorectal cancer: A retrospective cohort study - Aggarwal, Himani (World J Gastrointest Oncol, 2020)
BACKGROUND: Primary tumor location is a prognostic factor for metastatic colorectal cancer (mCRC). Post hoc analyses of mCRC clinical trials, including FIRE-3, CALGB/SWOG 80405, suggest that primary tumor location is also predictive of survival benefit with cetuximab or bevacizumab in combination with 5-fluorouracil-based chemotherapy. AIM: Evaluate prognostic/predictive roles of primary tumor location in real-world mCRC patients treated with cetuximab or bevacizumab plus 5-fluorouracil-based chemotherapy. METHODS: This retrospective cohort study selected patients with KRAS wild-type mCRC who initiated first-line therapy with cetuximab or bevacizumab in combination with 5-fluorouracil/leucovorin/irinotecan (FOLFIRI) or 5-fluorouracil/ leucovorin/oxaliplatin (FOLFOX) between January 2013 and April 2017 from the Flatiron Health electronic health record-derived database of de-identified patient-level data in the United States. Primary tumor location was abstracted from patients’ charts. Left-sided primary tumor location (LPTL) was defined as tumors that originated in the splenic flexure, descending colon, sigmoid colon, or rectum; right-sided primary tumor location (RPTL) was defined as tumors that originated from the appendix, cecum, ascending colon, hepatic flexure, or transverse colon. Propensity score matching was used to balance the baseline demographic and clinical characteristics between patients treated with cetuximab and patients treated with bevacizumab. Kaplan-Meier and Cox regression methods were used for survival analyses. RESULTS: A total of 1312 patients met the selection criteria. Of 248 cetuximab plus FOLFIRI or FOLFOX patients, 164 had LPTL and 84 had RPTL; of 1064 bevacizumab plus FOLFIRI or FOLFOX patients, 679 had LPTL and 385 had RPTL. Cetuximab LPTL and RPTL patients were more likely to receive FOLFIRI vs bevacizumab patients (LPTL: 64.0% vs 24.3%; RPTL: 76.2% vs 24.9%, P < 0.001). Stage at initial diagnosis was different between cetuximab RPTL vs bevacizumab RPTL patients (P < 0.001); cetuximab RPTL patients were more likely to have stage III disease (44.0% vs 22.6%), while bevacizumab RPTL patients were more likely to have stage IV disease (65.7% vs 48.8%). Cetuximab RPTL patients were more likely to have a documented history of adjuvant chemotherapy vs bevacizumab RPTL patients (47.6% vs 22.3%, P < 0.001). In the propensity score-matched sample, median overall survival (OS) was 29.7 mo (95%CI: 26.9-35.2) for LPTL patients vs 18.3 mo (95%CI: 15.8-21.3) for RPTL patients (P < 0.001). Median OS was 29.7 mo (95%CI: 27.4-NA) for cetuximab LPTL patients vs 29.1 mo (95%CI: 26.6-35.6) for bevacizumab LPTL patients (HR = 0.87; 95%CI: 0.63-1.19; P = 0.378) and 17.0 mo (95%CI: 12.0-32.6) for cetuximab RPTL patients vs 18.8 mo (95%CI: 15.8-22.3) for bevacizumab RPTL patients (HR = 1.00; 95%CI: 0.68-1.46; P = 0.996). The interaction of treatment and primary tumor location was not significant in the Cox regression. CONCLUSION: In this real-world mCRC cohort, the prognostic role of primary tumor location was substantiated, but not the predictive role for treatment with cetuximab vs bevacizumab in combination with 5-fluorouracil-based chemotherapy.